Bioavailability of iodine to mint from soil applied with selected amendments. Issue 1 (1st January 2019) - Mohiuddin, Muhammad; Irshad, Muhammad; Ping, An; Hussain, Zahid; Shahzad, Muhammad
ABSTRACT: The objective of this study was to investigate the bioavailability of iodine (I) after applying different soil amendments. The effectiveness of organic and inorganic I sources on I concentration of mint was compared. Soil was amended with sawdust, rice husk, charcoal, wood ash and gypsum at the rate 10 t ha-1. Results showed that the use of soil amendment significantly enhanced mint biomass. The biomass yield among amendments was in the order of charcoal > wood ash > sawdust > rice husk > gypsum > no-amendment. Amendments also significantly increased I concentration in plants. Iodine concentrations in mint shoot were higher in wood ash and charcoal than other treatments. Iodine contents in plants were higher with inorganic iodine than organic source. Iodine concentrations in shoot were associated with soil CEC and organic matter. This study indicated that a suitable soil amendment can be used for better I bioavailability.